The effects of buy-outs on employment: A dynamic Approach - Petrianidis, Panagiotis (2007)
Buy-out deals have now become a global phenomenon. From the first deals occurring in the US market in the early 1980s, these transactions have diffused around the world to the UK, continental Europe and the big Asian markets. As the size of the markets and individual deals is getting bigger, the impacts of these transactions are becoming more significant, attracting the attention of the media, regulators, scholars and managers. The effect of these transactions on the employees of target firms is a highly debated issue recently mainly due to the lack of transparency, the tight monitoring and the highly aggressive form of capitalism (Mathiason, 2007) that private equity firms represent. As more and more employees are working for buyout targets - around 850,000 employees in Europe (CMBOR data) -studies of the effects on employment are important. The purpose of this dissertation is to examine the effects of various types of buyout transactions that took place in the UK between 1991 and 2004, on employment. The goal is threefold. The first issue under investigation is whether buyouts have a positive or negative effect on employment. Secondly, the possible different effects of the various kinds of buyout transactions are examined. More importantly, the analyses are done in a dynamic manner, researching the effect of these transactions on employment on a yearly basis post-buyout. In this way, possible patterns of the employment effects are examined. The results show that buyouts in general have a positive impact on employment which is consistent though time. MBO firms account for this result, as they differ significantly from MBI firms, which do not differ from the non-buyout control sample.